The Role of Work-Life Balance and Job Satisfaction On The Organizational Commitment of Working Mothers as Early Childhood Education (ECCE) Teachers - Realdy, Muhamad; Wahidin Alfilizy , Fajar; Suzana , Anna (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to determine how much influence work-life balance and job satisfaction have on organizational commitment to working mothers as Early Childhood Education (ECCE) teachers. The research approach used quantitative descriptive, data collected from questionnaires with the data analysis method Structural Equations Modeling Partial Least Square (SEM-PLS). The results show that work-life balance has a significant effect on organizational commitment with a value of 2,734 > 1.96 or P values of 0.006 < 0.05, then H1 is accepted, namely work-life balance affects organizational commitment. Furthermore, job satisfaction affects organizational commitment with a value of 2,251 > 1.96 or P values of 0.024 < 0.05, then H2 is accepted, namely Job Satisfaction affects organizational commitment.